Changes in the Work Environment for Creativity During Downsizing - Amabile, Teresa M.; Conti, Regina (Academy of Management Journal, 1999)
This study examined the work environment for creativity at a large high-technology firm before, during, and after a major downsizing. Creativity and most creativity-supporting aspects of the perceived work environment declined significantly during the downsizing hut increased modestly later; the opposite pattern was observed for creativity-undermining aspects. Stimulants and obstacles to creativity in the work environment mediated the effects of downsizing. These results suggest ways in which theories of organizational creativity can be expanded and ways in which the negative effects of downsizing might be avoided or alleviated.